Redistribution of nutrient elements of gray forestal soil under grain crops in short-rotation crop rotations under different fertilization systems - О. Y. КАCHМАR; А. О. DUBYTSКА; М. М. SHCHERBА; І. V. SАVЕRYN; О. V. ТАRАVSКА; А. І. VОVК; Z. О. КОТYК (Передгірне та гірське землеробство і тваринництво, 2022)
In the conditions of short-rotation crop rotations, the influence of fertilization systems and precursors on the nutrient regime of grey forestal soil under winter wheat and spring barley was investigated.